2014
DOI: 10.2503/jjshs1.ch-107
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Blossom-end Rot in Relation to the Water-soluble Calcium Concentration in Tomato Fruits as Affected by Calcium Nutrition and Cropping Season

Abstract: To understand the factors affecting the incidence of blossom-end rot (BER), the effect of the Ca/K ratio (4/12-12/4, in me·L -1 ) in nutrient solutions and Ca concentration in fractions in the distal part of young tomato fruits immediately before BER symptoms appear were investigated for three seasons. The rate of BER incidence increased with a decrease in the Ca/K ratio in the supplied solutions in the summer and spring, but little difference was observed in the winter. Ca concentration was highest in winter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 23 publications
6
24
1
Order By: Relevance
“…Similar to our previous report (Yoshida et al, 2014), increased Ca concentration in the nutrient solution significantly increased Ca absorption but decreased K absorption (Table 3). The varied Ca/K ratios in the nutrient solutions did not affect plant absorption of water and other major elements (data not shown).…”
Section: Apparent Nutrient Absorptionsupporting
confidence: 91%
See 4 more Smart Citations
“…Similar to our previous report (Yoshida et al, 2014), increased Ca concentration in the nutrient solution significantly increased Ca absorption but decreased K absorption (Table 3). The varied Ca/K ratios in the nutrient solutions did not affect plant absorption of water and other major elements (data not shown).…”
Section: Apparent Nutrient Absorptionsupporting
confidence: 91%
“…Similar to our data previously described for the cultivar 'House Momotaro' (Yoshida et al, 2014), Ca in nutrient solution indicated a promotive effect on water-soluble Ca in both cultivars. The increase in the order of truss and temperature also had negative effects on water-soluble Ca in both cultivars.…”
Section: Factors Affecting Water-soluble Ca Concentration In the Distsupporting
confidence: 90%
See 3 more Smart Citations